Diversity of Belonging in Europe Public Spaces, Contested Places, Cultural Encounters - Eckersley, Susannah; Vos, Claske (Critical Heritages of Europe, 2023)
Diversity of Belonging in Europe analyzes conflicting notions of identity and belonging in contemporary Europe. Addressing the creation, negotiation, and (re) use of diverse spaces and places of belonging, the book examines their fascinating complexities in the context of a changing Europe. Taking an innovative interdisciplinary approach, the volume examines renegotiations of belonging played out through cultural encounters with difference and change, in diverse public spaces and contested places. Highlighting the interconnections between social change and culture, heritage, and memory, the chapters analyze multilayered public spaces and the negotiations over culture and belonging that are connected to them. Through analyses of diverse case studies, the editors and authors draw out the significance of the participation or exclusion of differing community, grassroots, and activist groups in such practices and discourses of belonging in relation to the contemporary emergence of identity conflicts and political uses of the past across Europe. They analyze the ways in which people's sense of belonging is connected to cultural, heritage, and memory practices undertaken in different public spaces, including museums, cultural and community centres, city monuments and built heritage, neglected urban spaces, and online fora. Diversity of Belonging in Europe provides a valuable contribution to the existing bodies of work on identities, migration, public space, memory, and heritage. The book will be of interest to scholars and students with an interest in contested belonging, public spaces, and the role of culture and heritage. Susannah Eckersley is Senior Lecturer at Newcastle University, UK, an Associated Research Fellow at the Leibniz Centre for Contemporary History (ZZF) in Potsdam, Germany, and the Project Leader of en/counter/points - a collaborative European research project on public spaces and belonging funded by HERA. Her expertise is in memory, museums, difficult heritage, migration, identities, and belonging. Claske Vos is an anthropologist and Assistant Professor in the Department of European Studies at the Humanities Faculty of the University of Amsterdam, the Netherlands. Her current work focuses on the intersection of EU funding, cultural activism, and enlargement. Her expertise is in European cultural policy, cultural heritage, Southeast Europe, and European identity formation.